Digital models of the consult-organization of management in the company - T. Rostovskaya; I. Groshev; Yu. Krasovskii (Цифровая социология)
The main segmental areas of activity of a consultant, invited by the head of the company for a fundamental correction of the organization of management in the context of the transition to digital format have been analyzed. The previous experience in management consulting has been rethought for application in modern, digital conditions for improving organizational management. This issue is extremely relevant for the entire consulting community, which is currently experiencing a serious crisis. The article has been addressed, first of all, to colleagues from the National Guild of professional consultants, who are looking for new methodological approaches, developing packages of new consult-competencies and new options for establishing contacts with potential customers. The previous developments have been adapted, namely: visual digital models for clearer visual support of the negotiation processes in business communication with the Customer. In the first digital model a general consulting approach to understanding management in a crisis and post-crisis period of organizing management in the process of mastering digital features of management relations has been introduced. In the second digital model, the positions of transition from a non-digital to digital format have been specified. In the third digital model the meaningful positions of the digital format in management consulting have been demonstrated. In the fourth digital model, the main contradiction in the organization of management has been identified, which must be submitted to the Customer for a final understanding of the situations, that arise. All four digital models are interrelated and help deeply understand the problems of the transition of the company from one state to another. These models “visualize” the negotiation process with the Customer, helping to quickly establish business contacts, as well as significantly reducing the time of the negotiation process.